Tris(ethylenediammonium) bis[(2-aminoethyl)ammonium] bis[bis(μ(5)-hydrogen phosphato)penta-μ(2)-oxido-decaoxidopentamolybdenum(VI)] decahydrate - Lu, Jing (International Union of Crystallography, 2010)
The title compound, (C(2)H(10)N(2))(3)(C(2)H(9)N(2))(2)[Mo(5)(HPO(4))(2)O(15)]·10H(2)O, was prepared under hydrothermal conditions at pH 5.0. The structure contains mono- and diprotonated ethylenediamine cations, [Mo(5)O(15)(HPO(4))(2)](4−) anions and uncoordinated water molecules. The [Mo(5)O(15)(HPO(4))(2)](4−) heteropolyoxometallate anion is made up of five MoO(6) octahedra sharing an edge and forming a ring, which is closed by common corners of the terminal MoO(6) octahedron. The ring is topped on both sides by two slightly distorted PO(4) tetrahedra, sharing three corners with three MoO(6) octahedra. The terminal oxygen atoms of the PO(4) units are protonated. Together with the anions, the water molecules and the ethylenediammonium cations are involved in N—H⋯O and O—H⋯O hydrogen bonding, forming a three-dimensional supramolecular network.